The Effect of Parenting Toward Students Mathematics Learning Achievement on Grade VII Students of SMPN 4 Sungguminasa - Mohammad Ardani Samad; Mangindara Mangindara (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
This research is an Ex-post Facto research with a quantitative approach and a comparative causal research design. This study aims to determine whether there is a parenting effect toward students mathematics learning achievement on grade VII students of SMPN 4 Sungguminasa. The population used in this study were all students on grade VII of SMPN 4 Sungguminasa, there are 349 students. The sample in this study was 64 students. Sampling using a random sampling technique. Data collection used the questionnaire and documentation method. Before data analysis, first do testing of the analysis requirements includes the normality and homogeneity tests. The data analysis technique used to test the hypothesis is Analysis  Variant (ANOVA) with one way type (One Way Anova). The results showed that there was a parenting effect toward students mathematics learning achievement on grade VII students of SMPN 4 Sungguminasa. This is indicated by the value of Fcount (31.375)>Ftable (3.32) and the Sig value is 0.000 <0.05 which means that there are significant differences in mean of all parenting groups.